Structure elucidation and 13c NMR assignment of an 1,2,4-oxadiazole substituted pyrazole - Neidlein, Richard; Kramer, Walter; Li, Sheng (Journal of heterocyclic chemistry, 1998)
The orientation of the substituent groups in an 1,2,4-oxadiazole substituted pyrazole, formed by reaction of a phenylnitrile oxide with an unsymmetrically substituted hydrazine is determined. One-dimensional methods as the selective INEPT and 13C1H nOe experiments are used. Both techniques provide also an unambiguous assignment of the 13C nmr spectrum.
Im Titel ist die Zahl "13" hochgestellt
Gesehen am 10.07.2023